WINTER RYE BREEDING IN YAKUTIYA - E. I. Vakhrameeva; L. V. Petrova; E. A. Eremeeva; V. I. Vladimirov (Зерновое хозяйство России, 2018)
The article gives the results of breeding of middle maturing, winter resistant, short stem winter rye variety which is stable to abiotic and biotic stressores with grain productivity 1,5-2,0 t/ha and high qualitative forage in the conditions of the Far North. The results of competitive variety testing between hybrids and a standard variety ‘Sitnikovskaya’ in grain and green mass (manure) have been presented. Biological characteristics of winter rye growth and development turned to be better than those of other grain crops and they are suitable for growing in dry conditions of Yakutiya. Using the method of backcrossing in hybridization of short stem, productive varieties and hybrids with a winter resistant donor ‘Sitnikovskaya’ it’s possible to breed new winter resistant, short stem, productive varieties suitable for growing in extreme conditions of  Yakutiya. Winter resistance of new varieties was about 99,2-99,8%. The height of the plants was about 107-110 cm, whereas a standard variety ‘Sitnikovskaya’ was 130 cm. The varieties hybridized with short stem productive cultivars of SibRIPG are resistant to lodging and produce high yields of grain and green mass. For three years these future varieties produced 30,2-32,2 t/ha of green mass in average, while the standard variety produced 29 t/ha, and exceeded the standard figure on 4,1%.  For the period grain productivity of new varieties was 4,28-4,59 t/ha, whereas the standard variety produced only 3,46 t/ha, that exceeded the standard one on 23-32%. The number of seeds per a ear was increased to 36-40 pcs and the ear length was 8,4-8,6 cm. The resistance to lodging of new varieties and hybrids was 9 points when the standard variety had only 3 points.